The role of collective action and property rights in climage change strategies - Meinzen-Dick, Ruth S.; Markelova, Helen; Moore, Kelsey (International Food Policy Research Institute, 2010)
The well-documented threats posed by climate change are serious and potentially devastating to the global community. The geographic areas that are most susceptible to the effects of climate change, such as increased droughts and flooding, are also the regions where the majority of the world's poor live. Evidence suggests that these effects may be especially severe for disadvantaged communities in developing countries that have few assets, such as fiscal resources and physical capital, and few income diversification opportunities, which severely limits their ability to cope or adapt to climate changes.